The study of cerebral hemodynamic and neuronal response to visual stimulation using simultaneous NIR optical tomography and BOLD fMRI in humans - Zhang, Xiaofeng (2005)
The integration of near-infrared (NIR) and functional MRI (fMRI) studies is potentially a powerful method to investigate the physiological mechanism of human cerebral activity. However, current NIR methodologies do not provide adequate accuracy of localization and are not fully integrated with MRI in the sense of mutual enhancement of the two imaging modalities. Results are presented to address these issues by developing an MRI-compatible optical probe and using diffuse optical tomography for optical image reconstruction. We have developed a complete methodology that seamlessly integrates NIR tomography with fMRI data acquisition. In this paper, we apply this methodology to determine both hemodynamic and early neuronal responses in the visual cortex in humans. Early results indicate that the changes in deoxyhemoglobin concentration from optical data are co-localized with fMRI BOLD signal changes, but changes in oxyhemoglobin concentration (not measurable using fMRI) show interesting spatial differences.